Management By the Customs Authorities in Poland of Imports and Exports of Flora and Fauna in The Light of The Provisions of The Washington CITES Convention - Magda LIGAJ; Małgorzata CHACKIEWICZ (Communications of International Proceedings, 2023)
The article consists of four parts. The first section on the legal provisions on imports and export of endangered species of plants and animals. The second part presents the essence of the smuggling of endangered plant and animal species. The third chapter presents cases of flora and fauna smuggling prevented by customs authorities in Poland. The final part of the article contains examples of fauna and flora trade and conclusions from the research study.
Keywords: endangered species; flora; fauna; natural environment